Dockland Transformation Adaptive Reuse of the Free Trade Wharf, River Thames, London - Gordon Ashworth; Bob Burnham (Oz, 1981)
Introduction. This project is an entry for an ideas competition for the adaptive reuse of a warehouse as a community recreation center in London's Docklands...